A systematic method of evaluation of the Chinese natural gas supply security. (1st March 2016) - Lu, Weiwei; Su, Meirong; Fath, Brian D.; Zhang, Mingqi; Hao, Yan
Highlights: Ecological network analysis is adopted to evaluate natural gas supply security. A network model of natural gas supply system in China is established. The contributions of different compartments to supply security are ranked. The relationships among different compartments in the network are analyzed. Suggestions based on scenario analysis are given to improve supply security. Abstract: As a relatively clean energy, natural gas will be increasingly in demand to meet short-term low-carbon targets. The gap between the demand and supply of natural gas will be increasingly scrutinized, which highlights the significance of natural gas supply security. Considering the extensive connections among various aspects related to natural gas supply and the complex interactions behind these connections, ecological network analysis was applied to simulate the natural gas supply system in China and systematically measure its overall security level. Network Information Analysis, Structural Analysis, and Utility Analysis were conducted. It is found that the Chinese natural gas supply security increased during 2000–2011. In terms of the influence of different compartments on the whole natural gas supply system, in order from the largest to smallest influence they are: supply sources, consumption sector, refining, and reserve sectors. And the relationships among compartments became stronger in the later stage than that in the earlier stage of the study period. Suggestions on improving China's natural gas supply security were proposed based on the results and further scenario analysis. The network model developed herein is a new perspective for natural gas supply security assessment, which can be used as guidance for policy making.